Tear production during the neonatal period - (:unkn) unknown (ELSEVIER SCIENCE INC, 2002)
PURPOSE: To measure tear secretion in term and preterm infants to assess whether tear secretion correlates with the maturity of the infants and to evaluate the changes in tear production during the neonatal period. DESIGN: Prospective, observational case series. METHODS: Ninety-six term and 22 preterm medically stable infants were studied. Post conceptional age and birth-weight of each infant were recorded. Tear secretion was measured by the Schirmer test before (total tear secretion) and after (basal tear secretion) the instillation of topical anesthetic agent. Both eyes were tested consecutively. The initial tear measurements were performed within the first 2 days of life, and tear measurements were repeated at 2 weeks and 4 weeks after birth. RESULTS: The mean total tear production was 16.3 (+/-3.6) mm in term and 7.4 (+/-3.2) mra in preterm infants. The mean basal tear production was 7.3 (+/-3.2) mm in term and 3.5 (+/-1.3) mm in preterm infants. Total tear secretion significantly correlated with birth-weight (r, 0.42, P = .04) and post-conceptional age (r, 0.56, P = .006) in preterm infants. For term infants, total tear secretion significantly increased at 2 weeks (18.1 +/- 3.4 mm, P < .001) and 4 weeks (19.5 +/- 4.1 mm, P < .001) after birth. For preterm infants, a significant increase in total tear production was observed at the fourth week (11.5 +/- 3 mm, P < .001). CONCLUSION: Tear production in newborns depends on the maturity of the infants and increases substantially during the neonatal period. Preterm infants have reduced tear secretion compared with term infants. (C) 2002 by Elsevier Science Inc. All rights reserved.
Keywords: TERM